Jesus and Mary reimagined in early Christian literature - Robbins, Vernon K. (Vernon Kay), 1939-; Potter, Jonathan M. (Atlanta : SBL Press, 2015)
These essays explore diverse storylines of Jesus, Mary, and other figures in texts from the first through third centuries. From priestly beginnings at the temple in Luke to the enigmatic figure of the cross of light in Acts of John, early Christians found multiple ways to tell their story and depict the actions of God in the context of their emerging beliefs. By reconfiguring and relocating traditional texts and topoi, each of the works examined here creates new blends of emerging Christian rhetorical dialects. The result is a wide variety of images and stories that enrich and enliven discourse, belief, and practice as Christians move into their creedal discussions, debates, and decisions during the fourth century. -- from back cover.
Priestly discourse in Luke and Acts / Vernon K. Robbins -- Bodies and politics in Luke 1-2 and Sirach 44-50 : men, women, and boys / Vernon K. Robbins -- Who am I to be blessed? : Mary as blessed mother in the protevangelium of James / Christopher T. Holmes -- Temple virgin and virgin temple : Mary's body as sacred space in the protevangelium of James / Meredith Elliott Hollman -- From prophetic hymns to death at the altar : Luke 1-2 and protevangelium of James / Michael K.W. Suh and Vernon K. Robbins -- Naked divinity : the transfiguration transformed in the Acts of John / Jonathan M. Potter -- Christ as cosmic priest : a sociorhetorical examination of the crucifixion scenes in the Gospel of John and Acts of John / Thomas Jared Farmer -- Response : Luke and the protevangelium of James / Ronald F. Hock -- Response : The Gospel of John and the Acts of John / Susan E. Hylen -- Rhetorical discourses in Gospel of John and Acts of John : a response / L. Gregory Bloomquist.
Includes bibliographical references (pages 313-322) and indexes.
Print version record.
Master record variable field(s) change: 050
Keywords: Jesus Christ -- Biblical teaching; Mary, -- Blessed Virgin, Saint -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Jesus Christ; Mary, -- Blessed Virgin, Saint; Bible; RELIGION -- Biblical Studies -- New Testament; Biblical teaching; Electronic books; Criticism, interpretation, etc